2020
DOI: 10.1039/d0cp00546k
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional C3N based sub-10 nanometer biosensor

Abstract: The current observation demonstrates the usefulness of the two-dimensional C3N system as a next generation bio-sensor for the sequencing of various nucleobases, offering new leads for future developments in bioelectronics, superior sensing architectures and sustainable designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Also, the folic-acid-modified C 3 N dots can be selectively endocytosed by tumor cells, which finally lead the cell to die . Similarly, 2D C 3 N could be utilized as a biosensor . Despite their diverse applications in biological systems, so far there are very limited studies or evidences to disclose the interaction dynamics and/or potential molecular mechanism of biomolecules binding to carbon nitride compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the folic-acid-modified C 3 N dots can be selectively endocytosed by tumor cells, which finally lead the cell to die . Similarly, 2D C 3 N could be utilized as a biosensor . Despite their diverse applications in biological systems, so far there are very limited studies or evidences to disclose the interaction dynamics and/or potential molecular mechanism of biomolecules binding to carbon nitride compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The two-dimensional carbon nitride C 3 N (also named as polyaniline) nanosheet composed of the basic unit of a benzene ring surrounded by six nitrogen atoms, which was experimentally polymerized by anilines (as illustrated in Figure a). Herein, we employed a dsDNA segment with the sequence (ATCG) 4 as a model to investigate the potential effect of the C 3 N nanosheet to dsDNA. Two systems were constructed as displayed in Figure b,c with the orientation of dsDNA being rotated (perpendicular and parallel to C 3 N nanosheet), and each of them was studied by three independent 500 ns-length atomistic MD simulations.…”
Section: Resultsmentioning
confidence: 99%
“…32 In addition, 2D C 3 N could be utilized as a biosensor for the sequencing of various nucleobases. 33 Despite their comprehensive applications in biomedicine, there were by far very few studies or evidence to disclose the effect of C 3 N nanomaterials to biomolecules. Our recent work probed the adhesion of the prototypical protein villin headpiece (HP35) to a C 3 N nanosheet and proved that the protein's structural integrity was partially denaturized during the adsorption, implying the possible harmfulness of C 3 N nanomaterials.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C 3 N and BC 3 are two graphene derivatives with similar honeycomb structures. They have good application prospects in batteries, gas separation, drug transport agents, biosensors, and so on. Because C 3 N and BC 3 are analogous in the structures, they are very easy to be integrated to construct heterostructures for novel nanodevices. In our previous work, we found that C 3 N is more capable of attracting biomolecules (DNA and protein) to form stable binding , than BC 3 .…”
Section: Introductionmentioning
confidence: 99%